Caregivers' experiences and perceptions of suicidality among their children and youth with fetal alcohol spectrum disorder - Harding, Kelly D.; Turner, Kailyn; Howe, Stephanie J.; Bagshawe, Mercedes Jayne; Flannigan, Katherine; Mela, Mansfield; McMorris, Carly A.; Badry, Dorothy (Frontiers in Psychiatry, 2022)
Individuals with Fetal Alcohol Spectrum Disorder (FASD) experience a range of biopsychosocial vulnerabilities that can increase the possibility of adverse life outcomes, including a heightened risk of suicidality. In this study, we explored the lived experiences of caregivers of children and youth with FASD and suicidality, including their perceptions of their child and youth's suicidal experiences. Between March and June 2021, six comprehensive, semi-structured interviews were conducted with five caregivers of children and youth with FASD (Mage = 14.5 years, range 11–22) who were currently experiencing suicidality or had a history of suicidality. Data were analyzed using interpretative phenomenological analysis and then developed into a composite vignette informed and organized by the social-ecological suicide prevention model (SESPM). The composite vignette revealed the narratives of families living with and caring for children and youth with FASD who experience suicidality in relation to the complex and intersectional individual, relational, community, and societal level contextual and protective factors. Findings from this study highlight the critical need for comprehensive FASD-informed suicide prevention and intervention approaches to promote the mental health and wellbeing of children and youth with FASD and their caregivers.